1997
DOI: 10.1164/ajrccm.156.6.9610117
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Bronchoscopic Techniques in the Diagnosis of Ventilator-associated Pneumonia to Reduce Antibiotic Use

Abstract: In intensive care units, a large proportion of antibiotics are prescribed for presumed episodes of ventilator-associated pneumonia (VAP). VAP is usually diagnosed on a combination of clinical, radiographic, and microbiologic criteria with a high sensitivity but low specificity for VAP. As a result, patients may receive antibiotics unnecessarily. Specificity can be increased by the addition of quantitative cultures of samples of protected specimen brush (PSB) and bronchoalveolar lavage (BAL) to the diagnostic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(70 citation statements)
references
References 17 publications
4
60
0
5
Order By: Relevance
“…As such, negative invasive test results ostensibly identify patients who can have antibiotic drug therapy safely discontinued, whereas positive test results indicate a requirement for continued treatment. Despite the lack of demonstrable mortality benefit, this approach seems to reduce antimicrobial use [59][60][61] and might lead to reduced total cost of care and less antibiotic resistance. Two studies 60,61 analyzing total cost of care of invasive diagnosis reached discordant conclusions principally on the basis of antimicrobial cost difference; both used bronchoscopy, adding substantially to the cost of diagnosis.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…As such, negative invasive test results ostensibly identify patients who can have antibiotic drug therapy safely discontinued, whereas positive test results indicate a requirement for continued treatment. Despite the lack of demonstrable mortality benefit, this approach seems to reduce antimicrobial use [59][60][61] and might lead to reduced total cost of care and less antibiotic resistance. Two studies 60,61 analyzing total cost of care of invasive diagnosis reached discordant conclusions principally on the basis of antimicrobial cost difference; both used bronchoscopy, adding substantially to the cost of diagnosis.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Outcome studies indicate that there are several factors related to mortality in VAP [2][3][4][5][6]. Delay in the initiation of therapy in pneumonia increases the risk of death in both community-acquired and nosocomial pneumonia [7,8].…”
mentioning
confidence: 99%
“…Importantly, negative microbiological results did not lead the physicians to discontinue empirical antibiotic therapy. 4 Nevertheless, several studies have confirmed that empirical antibiotics can be safely discontinued after 72 h or completely withheld 6,[31][32][33] with no adverse effect on VAP recurrence or mortality in subjects with negative cultures. Invasive diagnostic testing may increase physician confidence and provide valuable guidance for deciding whether to limit or discontinue antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%